Expert System Application for Troubleshooting and Maintaining Epson L3110 Printer - Henderi, Henderi; Rahwanto, Efana; Wahyuningsih, Tri; Badrianto, Achmad (LPPM Universitas Islam 45 Bekasi, 2021)
Many organizations are making changes by using information technology to support their business activities. Routine and uncomplicated activities tend to be carried out supported by computer-based applications. These activities include diagnosing damage and performing maintenance on the printer. This study aims to develop an Excel system application for fault diagnosis and maintenance of printers. The expert system printer damage diagnosis application in this study was developed based on a knowledge base. The research was conducted through the stages of needs analysis, design, implementation and testing. The test results show that the application developed is able to diagnose and display printer defects and provide solutions and fixed it.